2000
DOI: 10.1161/01.cir.101.10.1165
|View full text |Cite
|
Sign up to set email alerts
|

Troglitazone Improves Recovery of Left Ventricular Function After Regional Ischemia in Pigs

Abstract: Background-This study determined whether treatment of normal (nondiabetic) pigs with the insulin-sensitizing agent troglitazone improves recovery of left ventricular (LV) function after acute ischemia and whether such effects are associated with altered myocardial substrate metabolism. Methods and Results-Juvenile pigs (nϭ6) were treated with troglitazone (75 mg ⅐ kg Ϫ1 ⅐ d Ϫ1 PO) for 8 weeks. Untreated pigs (nϭ8) served as controls. Under anesthetized, open-chest conditions, pigs underwent 90 minutes of moder… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
60
1

Year Published

2002
2002
2016
2016

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 90 publications
(63 citation statements)
references
References 22 publications
2
60
1
Order By: Relevance
“…These results are in direct contrast to the beneficial effects on contractile function and energy metabolism and the absence of pro-arrhythmic effects observed after chronic pretreatment with troglitazone in the same model (10). The present findings also contrast with protective effects of either acute or chronic rosiglitazone treatment in myocardial ischemia/reperfusion in rats.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…These results are in direct contrast to the beneficial effects on contractile function and energy metabolism and the absence of pro-arrhythmic effects observed after chronic pretreatment with troglitazone in the same model (10). The present findings also contrast with protective effects of either acute or chronic rosiglitazone treatment in myocardial ischemia/reperfusion in rats.…”
Section: Discussioncontrasting
confidence: 99%
“…We found that pretreated pigs had significantly greater recovery of myocardial mechanical function and carbohydrate metabolism after ischemia and reperfusion than untreated pigs (10). There were no sustained ventricular arrhythmias among treated pigs.…”
mentioning
confidence: 66%
See 2 more Smart Citations
“…Our present data on cardiac energetics, however, are limited, and it is not clear whether acute rosiglitazone perfusion of isolated hearts reduces glycolysis or rapidly enhances uptake of accumulated lactate early in reperfusion. The latter may be more likely in view of the demonstration that treatment of pigs with troglitazone, another PPAR-␥ ligand, enhances uptake of lactate during reperfusion (27).…”
Section: Discussionmentioning
confidence: 99%